Analisis Kebutuhan pada Pengajaran Bahasa Inggris di PG-PAUD - Veri Hardinansyah Dja'far (Universitas Trunojoyo Madura, 2017)
English for Specific Purposes (ESP) learning process in higher education often administered less effectively. One of the contributing factors is the lack of learning plan so that learning is irrelevant to the field of science they are capable of. Therefore, it is necessary to start plan the learning by conducting need analysis based on students’ requirement on learning English. This study aims to find and describe the needs of students of English on early childhood education program. This research was carried by using qualitative descriptive approach. The objects of this research are students of early childhood education department class of 2016/2017 Universitas Trunojoyo Madura. Data were collected through questionnaires and conducting direct interviews. The collected data were classified so that the needs of the students on learning English can be identified, then described respectively. The results showed that (1) the English mastery of students was still relatively low, (2) 50% of students placed an increase in oral communication or speaking skills (Speaking) and 30% writing as a top priority in learning English for preparation to apply a job, (3) during learning English, students expected an improvement on their skills related to both oral and written. Based on these results, it is suggested to manage syllabus planning and the development of English teaching materials in early childhood education programs.